2018 Review of Program Design and Conditionality. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2019)
The 2018 Review of Program Design and Conditionality is the first comprehensive stocktaking of Fund lending operations since the global financial crisis. The review assesses program performance between September 2011 and end-2017. Programs during this period were defined by the protracted structural challenges faced by members and hampered by the persistently weak global environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet